2014
DOI: 10.1002/admi.201400433
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration Membranes with Structure‐Optimized Graphene‐Oxide Coatings for Antifouling Oil/Water Separation

Abstract: Fouling of ultrafiltration (UF) membranes in oil/water separation is a long‐standing issue and a major economic barrier to their use in a broad range of applications. Currently reported membranes typically show severe fouling, resulting from the strong oil adhesion on the membrane surface and/or oil penetration inside the membranes. This greatly degrades their performance and shortens service lifetime. Here, the use of graphene oxide (GO) as a novel coating material for the fabrication of fully recoverable, UF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(83 citation statements)
references
References 43 publications
0
83
0
Order By: Relevance
“…Underwater superoleophobicity is usually obtained by combining hydrophilic chemical composition and micro/nanoscale roughness on the membrane surface. [19,37,74,76,101,115,117,118] Due to the intrinsic rough surface structures, membranes are in fact expected to exhibit underwater superoleophobicity once their surfaces are effectively hydrophilized. A number of methods, such as hydrogel coating and salt-induced phaseinversion approach have been employed to fabricate membranes with underwater superoleophobicity.…”
Section: General Method: Improving Surface Hydrophilicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Underwater superoleophobicity is usually obtained by combining hydrophilic chemical composition and micro/nanoscale roughness on the membrane surface. [19,37,74,76,101,115,117,118] Due to the intrinsic rough surface structures, membranes are in fact expected to exhibit underwater superoleophobicity once their surfaces are effectively hydrophilized. A number of methods, such as hydrogel coating and salt-induced phaseinversion approach have been employed to fabricate membranes with underwater superoleophobicity.…”
Section: General Method: Improving Surface Hydrophilicitymentioning
confidence: 99%
“…A number of methods, such as hydrogel coating and salt-induced phaseinversion approach have been employed to fabricate membranes with underwater superoleophobicity. [19,31,102,115,117,119,120] For example, Gao et al reported a polyionized hydrogel coated copper mesh (underwater oil contact angle ~ 165 o ), which exhibited ultralow adhesion to viscous crude oils under an aqueous environment and could effectively separate a crude oil/water mixture with high flux and high oil rejection. [100] Blending and fabricating nanocomposite membranes.…”
Section: General Method: Improving Surface Hydrophilicitymentioning
confidence: 99%
“…[1][2][3][4][5][6][7] To address this issue, we need more effective methods of collecting and recovering insoluble oils ando rganics olvents from polluted water.R esearchers have developed numerous products and approaches forw ater purification, such as oil-containment booms, [8][9][10] absorbent compounds, [11][12][13] and variouso il/water separation techniques, [14][15][16][17] particularly those that are based on materialw ettability.F or example, severals uperhydrophobic/superoleophilic materials, including polyester-based compounds, [18,19] surfacemodified metal meshes, [20,21] and textiles, [22,23] have shown sat-isfactoryp erformancei ni solating oils that have ah igher density than water. [1][2][3][4][5][6][7] To address this issue, we need more effective methods of collecting and recovering insoluble oils ando rganics olvents from polluted water.R esearchers have developed numerous products and approaches forw ater purification, such as oil-containment booms, [8][9][10] absorbent compounds, [11][12][13] and variouso il/water separation techniques, [14][15][16][17] particularly those that are based on materialw ettability.F or example, severals uperhydrophobic/superoleophilic materials, including polyester-bas...…”
mentioning
confidence: 99%
“…This membrane can be recycled (greatert han five times) and featuress uperior efficiency (up to 97.9 %) for the separation of oils that have both higher and lower densities than water.T his work is the first proof-of-concept application of SuFEx to fabricate functional materials for environmentalr emediation.In recent years, water pollution caused by crude-oil spillsa nd the discharge of oily wastewaterh as become as erious global environmental problem. [1][2][3][4][5][6][7] To address this issue, we need more effective methods of collecting and recovering insoluble oils ando rganics olvents from polluted water.R esearchers have developed numerous products and approaches forw ater purification, such as oil-containment booms, [8][9][10] absorbent compounds, [11][12][13] and variouso il/water separation techniques, [14][15][16][17] particularly those that are based on materialw ettability.F or example, severals uperhydrophobic/superoleophilic materials, including polyester-based compounds, [18,19] surfacemodified metal meshes, [20,21] and textiles, [22,23] have shown sat-isfactoryp erformancei ni solating oils that have ah igher density than water. On the otherh and, inspired by the oleophobic properties of clam shells, researchers have also developed several superhydrophilic/superoleophobic or underwater superoleophobic materials for the recovery of oils and organic solvents that feature lower densities than waterb yi ncorporating high surface-energy functional groupso ntot he substrate.…”
mentioning
confidence: 99%
“…6000 L m ¹2 h ¹1 bar ¹1 . Yu and co-workers 45 illustrated ultrathin (a few tens of nanometers), "water-locking" GO coatings with the optimized hierarchical surface roughness that can minimize underwater oil adhesion on the membrane surface. Thus, ultrafiltration (UF) membranes with these novel GO coatings are obtained for antifouling oilwater separation by a facile vacuum filtration method.…”
Section: ¹1mentioning
confidence: 99%